2015
DOI: 10.1007/s12026-015-8664-y
|View full text |Cite
|
Sign up to set email alerts
|

Practical NK cell phenotyping and variability in healthy adults

Abstract: Human natural killer (NK) cells display a wide array of surface and intracellular markers that indicate various states of differentiation and/or levels of effector function. These NK cell subsets exist simultaneously in peripheral blood, and may vary amongst individuals. We examined variety amongst selected NK cell receptors expressed by NK cells from normal donors, as well as the distribution of select NK cell subsets and NK cell receptor expression over time in several individual donors. Peripheral blood mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
88
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(92 citation statements)
references
References 98 publications
4
88
0
Order By: Relevance
“…From our initial evaluation in 2004 and at all subsequent times evaluated, patient 1's CD56 bright subset was between 30% and 40% (27.9%-40.3%) of the NK cell population, in contrast to controls, which fell within the previously described range (4.1%-8.4%) (Figure 3, A-C, and ref. 25). Evaluation of hetero- (Figure 3, B-D).…”
Section: Resultsmentioning
confidence: 99%
“…From our initial evaluation in 2004 and at all subsequent times evaluated, patient 1's CD56 bright subset was between 30% and 40% (27.9%-40.3%) of the NK cell population, in contrast to controls, which fell within the previously described range (4.1%-8.4%) (Figure 3, A-C, and ref. 25). Evaluation of hetero- (Figure 3, B-D).…”
Section: Resultsmentioning
confidence: 99%
“…Angelo et al (20) analyzed a panel of 40 adult healthy donors with respect to NK cell subset distribution with the aim to establish normative ranges. They found that CD56 bright NK cells represent 8.56 6 6.90% (range, 0.63-38.32%) of peripheral blood NK cells, which is in accordance with older literature, but which also means that a percentage .10% (usually considered the upper limit) is observed quite frequently.…”
Section: Cd56mentioning
confidence: 99%
“…Human NK cells in peripheral blood are broadly classified as being CD56 + CD3 − and generally comprise 1–17% of mononuclear cells within peripheral blood of healthy adults (5). They are found primarily in two broadly defined phenotypic subsets, namely the CD56 bright and CD56 dim subsets, with the CD56 dim subset being the predominant one in peripheral blood.…”
Section: Human Nk Cell Subsetsmentioning
confidence: 99%
“…In some cases, namely GATA2 deficiency, a single gene defect may account for a widely variable clinical phenotype with regards to NK cell number. This likely is related to the effect of specific mutations but may also be reflective of innate plasticity of NK cell numbers and subsets over time, in even healthy individuals, and the infectious history of the patient (5, 23, 24). …”
Section: Classical Nkdmentioning
confidence: 99%
See 1 more Smart Citation